Hospital costs of complications after esophagectomy for cancer. Issue 4 (April 2017) - Goense, L.; van Dijk, W.A.; Govaert, J.A.; van Rossum, P.S.N.; Ruurda, J.P.; van Hillegersberg, R.
Abstract: Objective: The purpose of this study was to estimate the economic burden of postoperative complications after esophagectomy for cancer, in order to optimally allocate resources for quality improvement initiatives in the future. Methods: A retrospective analysis of prospectively collected clinical and financial outcomes after esophageal cancer surgery in a tertiary referral center in the Netherlands was performed. Data was extracted from consecutive patients registered in the Dutch Upper GI Cancer Audit between 2011 and 2014 (n = 201). Costs were measured up to 90-days after hospital discharge and based on Time-Driven Activity-Based Costing. The additional costs were estimated using multiple linear regression models. Results: The average total cost for one patient after esophagectomy was €37, 581 (±31, 372). The estimated costs of an esophagectomy without complications were €23, 476 (±6496). Mean costs after minor (47%) and severe complications (29%) were €31, 529 (±23, 359) and €59, 167 (±42, 615) (p < 0.001), respectively. The 5% most expensive patients were responsible for 20.3% of the total hospital costs assessed in this study. Patient characteristics associated with additional costs in multivariable analysis included, age >70 (+€2, 922, p = 0.036), female gender (+€4, 357, p = 0.005), COPD (+€5, 415, p = 0.002), and a history of thromboembolic events (+€6, 213, p = 0.028). Complications associated with a significant increase in costs in multivariable analysis included anastomotic leakage (+€4, 123, p = 0.008), cardiac complications (+€5, 711, p = 0.003), chyle leakage (+€6, 188, p < 0.001) and postoperative bleeding (+€31, 567, p < 0.001). Conclusions: Complications and severity of complications after esophageal surgery are associated with a substantial increase in costs. Although not all postoperative complications can be prevented, implementation of preventive measures to reduce complications could result in a considerable cost reduction and quality improvement.